IQ and obesity in adolescence: a population‐based, cross‐sectional study. Issue 6 (11th December 2013) - Goldberg, S.; Werbeloff, N.; Fruchter, E.; Portuguese, S.; Davidson, M.; Weiser, M.
Summary: What is already known about this subject: Low IQ is associated with high BMI in childhood. There are inconsistent findings on the association between low SES and high BMI. Youth with low IQ have been reported to have poorer health behaviors, such as poor nutrition and less physical activity. What this study adds: Low IQ is significantly associated with obesity for both male and female adolescents, though more strongly for female adolescents. Physical activity has a mediating effect on the association between low IQ and obesity among both male and female adolescents, though more strongly for male adolescents. The association between low IQ and obesity is strongest among adolescents from high SES backgrounds. Background: Previous studies have shown an association between low intelligence quotient (IQ), high body mass index and low socioeconomic status (SES). Objectives: This study examined the cross‐sectional association between IQ and obesity, exploring the roles of gender, SES and physical activity in this association. Methods: Subjects were 235 663 male and 169 259 female adolescents assessed by the Israeli military draft board. Results: Low IQ was significantly associated with increased odds of obesity among male (odds ratio [OR] = 1.44, 95% confidence interval [CI] = 1.36–1.52) and female adolescents (OR = 1.61, 95% CI = 1.51–1.73); this association was significantly stronger among female adolescents. Sobel tests indicated that physical activity had a significant mediating effect on this association for male and female adolescents, although more strongly for male adolescents. Dividing the sample according to SES, the association between low IQ and obesity was strongest in the high SES group (male adolescents: OR = 1.26, 95% CI = 1.10–1.43, female adolescents: OR = 1.61, 95% CI = 1.38–1.89), even when controlling for physical activity. Conclusions: The findings suggest that low IQ is associated with increased odds of obesity, particularly in female adolescents and in adolescents with high SES. Physical activity has a mediating effect on this association, although more strongly for male than for female adolescents. Public health measures on decreasing obesity might focus on these groups.